Naringenin alleviates liver ﬁbrosis by triggering autophagy-dependent ferroptosis in hepatic stellate cells - Ting Yu; Xuejia Lu; Yan Liang; Lin Yang; Yuehan Yin; Hong Chen (Heliyon, 2024)
Inhibition of activated hepatic stellate cells (HSCs) is a promising approach for treating liver fibrosis, and the ferroptosis has emerged as a pivotal mechanism to achieve this inhibition. The effects of naringenin, a flavonoid with anti-inflammatory properties, have not been thoroughly examined in liver fibrosis. Therefore, we used cholestasis model to study the effect of naringenin on liver fibrosis. Our findings demonstrated a significant exacerbation of liver tissue damage and fibrosis in mice subjected to bile duct ligation (BDL), accompanied by a substantial upregulation of fibrogenesis-related gene expression. Notably, naringenin administration markedly alleviated liver injury and fibrosis in these mice. Furthermore, naringenin exhibited inhibitory effects on the activation of HSCs, concurrently inducing ferroptosis. Importantly, naringenin significantly increased autophagic activity in HSCs. This effect was counteracted by co-administration of the autophagy inhibitor 3-MA, leading to a notable reduction in naringenin-induced HSC ferroptosis. In BDL model mice, naringenin demonstrated a mitigating effect on liver fibrosis, suggesting a potential correlation with naringenin-induced ferroptosis of HSCs. These results provide novel insights into the molecular mechanisms of naringenin-induced ferroptosis and highlight autophagy-dependent ferroptosis as a promising therapeutic strategy for liver fibrosis.